The widower's tale [large type] - Glass, Julia, 1956- (Center Point Pub., 2010)
Enjoying an active but lonely rural life, seventy-year-old Percy allows a progressive preschool to move into his barn and transform his quiet home into a lively, youthful community that compels him to reexamine the choices he made after his wife's death.